Stability ring lactone study of camptothecin and irinotecan in artificial media and Human plasma - Fatmi, Sofiane (Biopolymer Applications Journal, 2022)
Camptothecin is a promising anti-colorectal cancer agent. However, its use in clinical medicine is compromised by its low solubility and high instability in physiologicalmedia. The presentwork aimsto study the chemical stability of the camptothecin lactone ring (alone, encapsulated, and in solid dispersion) while comparing it to that of a reference analog irinotecan. This stability is studied in acidic (pH 2) and physiological (saline) media and Human plasma by high performance liquid chromatography (HPLC). Stability tests carried out on CPT alone, encapsulatedand in solid dispersion in artificial media and Human plasma demonstrate that ternary systems[CPT/β-CDs/PEG 6000 and CPT/PM-βCDs/PEG 6000] can lead to the protection of CPT lactone ring in physiological media and Human plasma for 72 hours. This protection is essential to the camptothecin therapeutic effect when administered in pharmaceutical form.